137PSignificant benefit of pyrotinib combined with SHR6390 in patients with multiline-resistant HER2-positive advanced gastric cancer. (24th November 2019) - Chen, Z; Xu, Y; Gong, J; Zhang, M; Tian, T; Zhang, X; Zhang, C; Gao, J; Shen, L
Abstract: Background: The aim of the present study was to explore the mechanism underlying the poor efficacy of pyrotinib, propose and validate a strategy for pyrotinib-combined therapy in patients with human epidermal growth factor receptor 2 (HER2)-positive gastric cancer (GC). Methods: Human GC cell lines and patient-derived xenograft (PDX) models were used to evaluate the antitumor activity and mechanisms of pyrotinib. One pyrotinib-refractory PDX model was established to explore the potential mechanisms underlying drug resistance, propose an optimal therapeutic strategy, and further validate in a phase I clinical trial (NCT03480256). Results: Pyrotinib exerted strong antitumor activity in HER2-positive GC cells and PDX models via suppressing the activation of the AKT/S6 signaling pathway. In addition, dysregulation of the cell cycle, represented by aberrant activation of the CCND1-CDK4/6-Rb axis, was found in the pyrotinib-refractory PDX model compared with the parental model. Then, combination therapy of pyrotinib with a CDK4/6 inhibitor (SHR6390) was proposed and its strong tumor growth inhibition was observed in the pyrotinib refractory-PDX model. Three HER2-positive GC patients after multiline therapies were subsequently enrolled in our clinical trial treatment with pyrotinib (400 mg/d for 28 days per cycle) combined with SHR6390 (100 mg/d for 21 days per cycle). After two cycles of therapy, two patients achieved a partial response (PR) and one patient achieved decreased stable disease (SD) with a progression-free survival of 120, 199, and 110 d, respectively. The common adverse events included leucopenia (grade 2 to 3), neutropenia (grade 2 to 4), anemia (grade 1 to 3), and thrombocytopenia (grade 1). Conclusions: This representative translational study suggests that a combination treatment of pyrotinib with SHR6390 may serve as a promising strategy for patients with HER2-positive GC after systematic treatment failure. The optimal drug doses and tolerability of this combination treatment will be explored in future studies. Legal entity responsible for the study: Zuhua Chen. Funding: The National Key Research and Development Program of China (No. 2017YFC1308900, 2017YFC0908400). Disclosure: All authors have declared no conflicts of interest.